2020
DOI: 10.1057/s41289-020-00145-3
|View full text |Cite
|
Sign up to set email alerts
|

Informal urbanism in the state of uncertainty: forms of informality and urban health emergencies

Abstract: Forms of informality—ranging from informal settlements to street vending and informal transport—have become integral, yet not necessarily limited to how cities of the global South work. Our aim in this paper is to explore the dynamics of informal urbanism in the face of the COVID-19 pandemic and the extent to which forms of informality can adapt in the state of uncertainty. This paper lies in the intersections of informal urbanism and urban design in relation to public health emergencies. This is an explorator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 48 publications
0
22
0
3
Order By: Relevance
“…The primary aim of this subject is to introduce a range of research methods concerning critical questions in the field of urban design. It also seeks to enable students to deepen their methodological understanding and critical thinking in relation to those forms of urbanism that have remained underexplored [60][61][62] and to the ways in which urban places work at the intersections between spatiality and sociality [63], between the measurable and the non-measurable [64], and between urban morphology and streetlife intensity [65,66]. Figure 1 illustrates the RMT subject in relation to other subjects in the MA UD.…”
Section: Urban Design Education and Research Methodsmentioning
confidence: 99%
“…The primary aim of this subject is to introduce a range of research methods concerning critical questions in the field of urban design. It also seeks to enable students to deepen their methodological understanding and critical thinking in relation to those forms of urbanism that have remained underexplored [60][61][62] and to the ways in which urban places work at the intersections between spatiality and sociality [63], between the measurable and the non-measurable [64], and between urban morphology and streetlife intensity [65,66]. Figure 1 illustrates the RMT subject in relation to other subjects in the MA UD.…”
Section: Urban Design Education and Research Methodsmentioning
confidence: 99%
“…According to the survey results, undertaking field site visits throughout the urban design studio subject has been considered helpful for learning experiences. This lends itself well to the discussion that field site visits are critical in enabling encounters between the shared body of knowledge in the field and the conditions of real cities, encouraging comparative approaches to the narratives of urban development, challenging the related urban design theories, and testing their relevance to design thinking and intervention [23,31,32]. We found that while using virtual platforms such as Google Earth and Google Street View can enable students to navigate the studio sites and conduct preliminary remote site analyses, face-to-face field site visits are favoured by many design studio students.…”
Section: Discussionmentioning
confidence: 82%
“…The urban ecology of the station areas in the western station areas comprises both formal and informal economies and shows how different forms of self-organised activities can loosen up the spatial striation of public space and maximise its affordances associated with the emergence of vibrant urbanity and economic productivity. Informal vending here is attracted to pedestrian flows mediated by urban attractions [37,51]. Such activities are often clustered in proximity to station entries and shopping centres and along the most accessible public spaces from the station.…”
Section: Discussionmentioning
confidence: 99%